Rhotacism and Lambdacism in Portuguese: The Process of Orthographic Standardization and Liquid Consonants - Justo Barreto, Débora Aparecida Dos Reis [UNESP]; Massini-Cagliari, Gladis [UNESP] (Springer Nature, 2023)
The purpose of this study is to promote a reflection on two phenomena that, in the contemporary Portuguese language, are the target of linguistic prejudice: rhotacism and lambdacism. In order to do so, it turns to the medieval stage of the language, thinking about how the process of orthographic standardization was decisive for the construction of a discriminatory attitude in the face of variation, since, in the Middle Ages, constructions such as groriosa and regla figured systematically in the medieval Galician-Portuguese songbooks and texts written only by the most erudite and privileged of that time.
Keywords: Archaic Portuguese; Lambdacism; Liquid consonants; Rhotacism